The Factors Influencing the Employment of University Students Graduating From Human Resource Management in Taian City, The People’s Republic of China - Hui, Cao Hui; Teerapornlertratt, Preyaporn; Kumboon, Buraporn (International Journal of Multidisciplinary in Management and Tourism, 2023)
This article aimed (1) to study factors affecting employment opportunities, (2) to study the requirements of the workplace and (3) to analyze and suggest to improve the employment of graduates majoring in human resource management. The sample was 267 undergraduate graduates of Taishan University majoring in human resources management from 2016 to 2022. They were selected by the Taro Yamane method of sample size calculation technology. The instrument for collecting data was the qualitative research method. Analysis of data by Descriptive statistics and Content Analysis. The research results were found as follows; 1. The study found that there are a total of two influencing factors. Personal qualities, including personal skills, knowledge level, and requirements of the enterprise, will have an impression on the improvement of employment ability of graduates majoring in human resource management; University factors, including employment policies, curriculum offerings, and employment services, can affect employment performance. 2. It was found that enterprises have job requirements for graduates majoring in human resource management. The job requirements and employment performance of graduates majoring in human resource management are in line with the requirements of the enterprise. The satisfaction of graduates majoring in human resource management is relatively high. The job requirements of graduates majoring in human resource management are in line with the university factors that affect employment. 3. It was found to be necessary to improve the personal quality of students, cultivate the professional practical ability, and build a practical basis for human resource management.